Generation of contractile forces by three-dimensional bundled axonal tracts in micro-tissue engineered neural networks - Chouhan, Dimple; Gordián Vélez, Wisberty J.; Struzyna, Laura A.; Adewole, Dayo O.; Cullen, Erin R.; Burrell, Justin C.; O’Donnell, John C.; Cullen, D. Kacy (Frontiers in Molecular Neuroscience, 2024)
Axonal extension and retraction are ongoing processes that occur throughout all developmental stages of an organism. The ability of axons to produce mechanical forces internally and respond to externally generated forces is crucial for nervous system development, maintenance, and plasticity. Such axonal mechanobiological phenomena have typically been evaluated in vitro at a single-cell level, but these mechanisms have not been studied when axons are present in a bundled three-dimensional (3D) form like in native tissue. In an attempt to emulate native cortico-cortical interactions under in vitro conditions, we present our approach to utilize previously described micro-tissue engineered neural networks (micro-TENNs). Here, micro-TENNs were comprised of discrete populations of rat cortical neurons that were spanned by 3D bundled axonal tracts and physically integrated with each other. We found that these bundled axonal tracts inherently exhibited an ability to generate contractile forces as the microtissue matured. We therefore utilized this micro-TENN testbed to characterize the intrinsic contractile forces generated by the integrated axonal tracts in the absence of any external force. We found that contractile forces generated by bundled axons were dependent on microtubule stability. Moreover, these intra-axonal contractile forces could simultaneously generate tensile forces to induce so-called axonal “stretch-growth” in different axonal tracts within the same microtissue. The culmination of axonal contraction generally occurred with the fusion of both the neuronal somatic regions along the axonal tracts, therefore perhaps showing the innate tendency of cortical neurons to minimize their wiring distance, a phenomenon also perceived during brain morphogenesis. In future applications, this testbed may be used to investigate mechanisms of neuroanatomical development and those underlying certain neurodevelopmental disorders.